Kevlar-polybenzoxazine aerogel and preparation method thereof

By combining Kevla nanofibers with polybenzoxazine aerogel, using sol-gel method and CO2 supercritical fluid drying technology, Kevla-polybenzoxazine aerogel with a three-dimensional nanoporous network structure was prepared, which solved the problem of insufficient mechanical strength of polybenzoxazine aerogel in high stress or extreme environments, achieved lightweight, high strength and ultra-low thermal conductivity, and had excellent thermal insulation and good mechanical properties.

CN119391040BActive Publication Date: 2025-03-25CHANGSHA RONGLAN MACHINERY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510005014.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-25
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing polybenzoxazine aerogels are insufficient in high stress or extreme environments, making it difficult to match the performance of high strength and low thermal conductivity.

Method used

Kevla-polybenzoxazine aerogel with a three-dimensional nanoporous network structure was prepared by combining Kevla nanofibers with bisphenol A-type benzooxazine monomers and using sol-gel method and CO2 supercritical fluid drying technology.

Benefits of technology

The lightweight, high strength and ultra-low thermal conductivity of Kevla-polybenzoxazine aerogel are achieved, with excellent thermal insulation and good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391040B_ABST
    Figure CN119391040B_ABST
Patent Text Reader

Abstract

The present invention discloses a Kevlar-polybenzoxazine aerogel and a preparation method thereof. The Kevlar-polybenzoxazine aerogel obtained by the preparation method of the present invention has high strength characteristics. Through the introduction of Kevlar nanofibers, a cross-linked interpenetrating structure is formed between the polymer of the selected benzoxazine monomer, which further improves the mechanical strength of the Kevlar-polybenzoxazine aerogel. Therefore, the Kevlar-polybenzoxazine aerogel prepared by the preparation method of the present invention has good mechanical properties, and the compressive stress can reach 3.974 MPa at 3% strain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic aerogel thermal insulation materials, and in particular relates to a Kevlar-polybenzoxazine aerogel and a preparation method thereof. Background Art

[0002] In the aerospace field, aircraft materials need to withstand extreme working environments, such as high temperature, high pressure, strong vibration and severe aerodynamic loads, which places extremely high demands on the performance of materials. With the increase in aircraft speed and flight altitude, traditional materials can no longer meet the needs of modern aerospace technology in terms of high temperature strength, heat resistance and thermal insulation. At present, high-performance materials that are both lightweight and high-strength, resistant and highly efficient are becoming the focus of research in this field.

[0003] Polybenzoxazine (PBz) aerogel is a new type of thermosetting aromatic polymer aerogel. It not only has the advantages of excellent heat resistance and chemical corrosion resistance derived from polybenzoxazine resin, but also has the characteristics of high specific surface area, high porosity, low density, and low thermal conductivity derived from aerogel (J. Mater. Sci, 2019, 54:12951-12961, ACS Appl. Nano Mater, 2021, 4(7): 7280-7288, J. Appl. Polym. Sci, 2021, 138(18):50333). Compared with the polymer aerogel derived from phenolic resin of the same family, polybenzoxazine aerogel has lower curing shrinkage and better dimensional stability during the gelation process because basically no by-products are produced during the polymerization process. At present, polybenzoxazine aerogel has been shown to have the potential to be used in many fields such as thermal insulation, adsorption, energy storage, and sensing (Adv. Colloid Interface Sci. 329 (2024): 103185). However, the use of polybenzoxazine aerogel alone still has the problem of insufficient mechanical strength under certain high stress or extreme environments.

[0004] Kevlar is a high-performance polymer material, also known as para-aramid (poly(p-phenylene terephthalamide), aramid-1414, also known as Kevlar). Its products include Kevlar long fiber, Kevlar paper, Kevlar cloth, etc. (China Papermaking, 2022, 41(11): 1-10.). Kevlar has the properties of self-extinguishing, high strength, high modulus, low temperature resistance, and high temperature resistance. It is currently commonly used in the field of military protection, such as bulletproof vests and bulletproof plates of armored vehicles. In particular, Kevlar nanofibers are also an ideal reinforcement material and are used in other polymer composites (Environmental Chemistry, 2023, 42(04):1239-1248).

[0005] Therefore, how to combine Kevlar nanofibers with polybenzoxazine aerogels to further improve the mechanical strength of polybenzoxazine aerogels while ensuring their low density, low thermal conductivity, and high-efficiency thermal insulation properties, and successfully synthesize Kevlar-polybenzoxazine aerogels with light weight, high strength, and high-efficiency thermal insulation has always been a technical challenge that researchers in this field need to pay attention to and overcome. Summary of the invention

[0006] In view of the problems of low strength of pure polybenzoxazine aerogel in the prior art and difficulty in matching low thermal conductivity with high strength, the present invention provides a Kevlar-polybenzoxazine aerogel and a preparation method thereof, which is a new type of Kevlar-polybenzoxazine aerogel and a preparation method thereof.

[0007] The technical solution of the present invention is as follows:

[0008] The Kevlar-polybenzoxazine aerogel of the present invention uses Kevlar nanofibers and bisphenol A benzoxazine monomers as raw materials, adopts organic solvents, respectively prepares Kevlar nanofiber solutions and benzoxazine monomer solutions as precursor solutions, adopts a sol-gel method, adds alkaline substances as dispersants for Kevlar nanofibers, and then adds acid substances as initiators for cationic ring-opening polymerization of polybenzoxazine aerogels, so as to promote the ring-opening polymerization of bisphenol A benzoxazine monomers at room temperature to form polybenzoxazine gel, and then obtains the Kevlar-polybenzoxazine aerogel with a three-dimensional nanoporous network structure, light weight, low thermal conductivity and high strength after aging, solvent replacement and CO2 supercritical fluid drying.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a Kevlar-polybenzoxazine aerogel comprises the following steps:

[0011] (1) Pour Kevlar nanofibers into an organic solvent containing an alkaline substance for dispersion, and stir at 20° C. to 60° C. until the fibers are uniformly dispersed, to obtain a Kevlar nanofiber solution having a mass concentration of 0.1 wt % to 10 wt %, as solution A;

[0012] The chemical structural formula of the Kevlar nanofiber is:

[0013] ;

[0014] The alkaline substance is one of potassium hydroxide, sodium hydroxide, triethylamine, tetramethylethylenediamine, sodium tert-butoxide, potassium tert-butoxide, potassium hexamethyldisilazide, and sodium hexamethyldisilazide;

[0015] The concentration of the alkaline substance in the organic solvent is 0.1 wt%~20 wt%;

[0016] The organic solvent is one of DMF, DMSO or NMP;

[0017] (2) Stirring a bisphenol A benzoxazine monomer at room temperature and fully dissolving it in an organic solvent to prepare a bisphenol A benzoxazine monomer solution having a mass concentration of 5 to 25 wt%, and then adding an acid substance as an initiator of the benzoxazine monomer, wherein the amount of the acid substance is prepared according to a molar ratio of bisphenol A benzoxazine monomer to the acid substance of 1:(1 to 3); stirring at 10°C to 30°C for 10 min to 15 min to obtain a polybenzoxazine sol, which is used as solution B;

[0018] The structural formula of the bisphenol A type benzoxazine monomer is as follows:

[0019] ;

[0020] When R1=OH, R2=CH3, it is bisphenol A type benzoxazine monomer structural formula Ⅰ;

[0021] When R1=OH, one of R2 is OH and the other is CH3, it is bisphenol A type benzoxazine monomer structural formula II;

[0022] When R1=OH, R2=OH, it is bisphenol A type oxazine monomer structural formula III;

[0023] The acid substance is one of hydrochloric acid, tannic acid, p-toluenesulfonic acid and boric acid;

[0024] (3) mixing the solution A obtained in step (1) and the solution B obtained in step (2) in a mass ratio of (0.2-1):1, and stirring at 10°C-30°C for 5 min-10 min to obtain a Kevlar-polybenzoxazine sol;

[0025] (4) The Kevlar-polybenzoxazine sol obtained in step (3) is transferred into a mold, sealed, and placed at 10°C to 30°C for gelation. After being placed for 15 h to 72 h for gelation (this time is referred to as the gelation time), an initial Kevlar-polybenzoxazine gel is obtained;

[0026] (5) aging the initial Kevlar-polybenzoxazine gel obtained in step (4) at 10° C. to 30° C. for 24 h to 96 h to obtain an aged Kevlar-polybenzoxazine gel;

[0027] (6) transferring the aged Kevlar-polybenzoxazine gel obtained in step (5) into a solvent containing a replacement solvent, covering the container with a lid and placing it in a water bath, and performing solvent replacement at 50° C. to 70° C. to obtain a final Kevlar-polybenzoxazine gel;

[0028] The replacement solvent is one of ethanol, acetone, isopropanol, and tert-butanol, the mass concentration of the replacement solvent is ≥95 wt%, the number of solvent replacements is 2 to 4 times, and the time interval is 6 h to 12 h;

[0029] (7) The final Kevlar-polybenzoxazine gel obtained in step (6) is subjected to CO2 supercritical fluid drying, wherein the CO2 supercritical fluid drying has a drying pressure of 8 MPa to 18 MPa, a temperature of 40°C to 60°C, and a drying time of 6 h to 18 h to obtain a Kevlar-polybenzoxazine aerogel having a density of 0.109 g cm -3 ~0.252 g cm -3 , thermal conductivity is 0.0182 W m -1 K -1 ~0.0343 W m -1 K -1 , the compressive stress is 1.871 MPa~3.974 MPa at 3% strain.

[0030] Furthermore, in step (1), the mass concentration of the Kevlar nanofiber solution is preferably 5.5 wt %; the alkaline substance is preferably potassium hydroxide; the concentration of the alkaline substance in the organic solvent is preferably 10 wt %; the organic solvent is preferably DMF; and the mixture is preferably stirred at 50° C. until uniformly dispersed.

[0031] Furthermore, in step (2), the polybenzoxazine sol is preferably obtained after stirring for 10 minutes.

[0032] Furthermore, in step (3), the mixture is preferably mixed at a mass ratio of 0.6:1 and stirred for 10 min.

[0033] Furthermore, in step (4), aging is preferably performed at room temperature for 48 h.

[0034] Furthermore, in step (6), the solvent replacement is preferably carried out at 60°C, the replacement solvent is ethanol or acetone, the number of solvent replacements is 3 times, and the time interval is 6 hours.

[0035] Furthermore, in step (7), the CO2 supercritical fluid drying preferably has a drying pressure of 12 MPa to 15 MPa, a temperature of 45°C to 55°C, and a drying time of 8 h to 10 h.

[0036] The present invention also relates to a Kevlar-polybenzoxazine aerogel, which is obtained by the above-mentioned method for preparing a Kevlar-polybenzoxazine aerogel. The Kevlar-polybenzoxazine aerogel has a three-dimensional nanoporous network structure, ultra-low thermal conductivity and high-efficiency thermal insulation performance, and has an excellent blocking effect on solid heat transfer and gas heat transfer. The density is 0.109 g cm -3 ~0.252 g cm -3 , thermal conductivity is 0.0182 W m -1 K -1 ~0.0343 W m -1 K -1 , has good mechanical properties, and the compressive stress is 1.871 MPa~3.974 MPa at 3% strain.

[0037] Compared with the prior art, the present invention has the following advantages:

[0038] 1. The preparation method of Kevlar-polybenzoxazine aerogel described in the present invention, wherein the obtained Kevlar-polybenzoxazine aerogel using organic solvent as solvent has a three-dimensional nanoporous network structure, ultra-low thermal conductivity and high-efficiency thermal insulation performance, and has an excellent blocking effect on solid heat transfer and gas heat transfer. The density of the Kevlar-polybenzoxazine aerogel prepared by the preparation method of the present invention is 0.109 g cm -3 ~0.252 g cm -3 , thermal conductivity is 0.0182 W m - 1 K -1 ~0.0343 W m -1 K -1 .

[0039] 2. The Kevlar-polybenzoxazine aerogel obtained by the preparation method of the present invention has high strength characteristics. Through the introduction of Kevlar nanofibers, a cross-linked interpenetrating structure is formed between the polymer of the selected benzoxazine monomer, which further improves the mechanical strength of the Kevlar-polybenzoxazine aerogel. Therefore, the Kevlar-polybenzoxazine aerogel prepared by the preparation method of the present invention has good mechanical properties, and the compressive stress can reach 3.974 MPa at 3% strain (in this field, the corresponding stress at 3% strain is usually used to evaluate the mechanical properties of the material. Therefore, the present invention will also use this value to compare the mechanical properties of the product aerogels obtained under different preparation conditions). BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The present invention is a general flow chart of the method for preparing the Kevlar-polybenzoxazine aerogel. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.

[0042] Embodiment 1:

[0043] A method for preparing a Kevlar-polybenzoxazine aerogel comprises the following steps:

[0044] (1) Pour 5.5 g of Kevlar nanofibers into 94.5 g of DMF with a concentration of 10 wt % potassium hydroxide for dispersion, and stir at 60 ° C until uniformly dispersed to obtain a Kevlar nanofiber solution with a concentration of 5.5 wt %, which is recorded as solution A;

[0045] (2) 5 g of bisphenol A benzoxazine monomer of structural formula I was fully dissolved in 95 g of DMF to obtain 100 g of 5 wt% bisphenol A benzoxazine monomer solution, and then 0.922 ml of hydrochloric acid was added to the benzoxazine monomer solution as an initiator (i.e., the molar ratio of bisphenol A benzoxazine monomer to hydrochloric acid was 1:1), and the mixture was stirred at room temperature for 15 min to obtain a polybenzoxazine sol, which was recorded as solution B;

[0046] (3) mixing solution A obtained in step (1) with solution B obtained in step (2), and stirring at room temperature for 5 min to obtain a Kevlar-polybenzoxazine sol (at this time, the mass ratio of solution A to solution B is 0.2);

[0047] (4) the Kevlar-polybenzoxazine sol obtained in step (3) is placed at room temperature and allowed to stand for about 30 hours, and then a gelation reaction occurs, causing the bisphenol A-type benzoxazine monomer to undergo ring-opening polymerization to obtain an initial Kevlar-polybenzoxazine gel;

[0048] (5) placing the initial Kevlar-polybenzoxazine gel obtained in step (4) at room temperature for 48 hours for aging to obtain an aged Kevlar-polybenzoxazine gel;

[0049] (6) The initial Kevlar-polybenzoxazine gel obtained in step (4) is transferred to a container filled with 98% ethanol, and after the lid is closed, the container is placed in a 60°C water bath for solvent replacement, and the solvent is replaced every 6 hours for three times; after the solvent replacement is completed, the gel is cooled to room temperature to obtain the final Kevlar-polybenzoxazine gel;

[0050] (7) The final Kevlar-polybenzoxazine gel obtained in step (6) is placed in a CO2 supercritical fluid drying device at a drying pressure of 13 MPa, a drying temperature of 50°C, and a drying time of 10 h to obtain a Kevlar-polybenzoxazine aerogel.

[0051] The density of the final prepared Kevlar-polybenzoxazine aerogel is 0.121 g cm -3 , thermal conductivity is 0.0199 Wm -1 K -1 , the compressive stress is 1.927 MPa at 3% strain.

[0052] Embodiment 2:

[0053] A method for preparing a Kevlar-polybenzoxazine aerogel comprises the following steps:

[0054] (1) Pour 0.1 g of Kevlar nanofiber into 99.9 g of DMF with a concentration of 10 wt% potassium hydroxide for dispersion, and stir at 60 °C until uniformly dispersed to obtain a Kevlar nanofiber solution with a concentration of 0.1 wt%, which is recorded as solution A.

[0055] (2) 5 g of bisphenol A benzoxazine monomer of structural formula I was fully dissolved in 95 g of DMF to obtain 100 g of 5 wt% bisphenol A benzoxazine monomer solution, and then 0.922 ml of hydrochloric acid was added to the benzoxazine monomer solution as an initiator (i.e., the molar ratio of bisphenol A benzoxazine monomer to hydrochloric acid was 1:1), and the mixture was stirred at room temperature for 15 min to obtain a polybenzoxazine sol, which was recorded as solution B;

[0056] (3) mixing solution A obtained in step (1) with solution B obtained in step (2), and stirring at room temperature for 5 min to obtain a Kevlar-polybenzoxazine sol, wherein the mass ratio of solution A to solution B is 0.6;

[0057] (4) The Kevlar-polybenzoxazine sol obtained in step (3) is placed at room temperature and allowed to stand for about 24 hours to undergo a gelation reaction, causing the bisphenol A-type benzoxazine monomer to undergo ring-opening polymerization to obtain an initial Kevlar-polybenzoxazine gel;

[0058] (5) placing the initial Kevlar-polybenzoxazine gel obtained in step (4) at room temperature for 48 hours for aging to obtain an aged Kevlar-polybenzoxazine gel;

[0059] (6) The initial Kevlar-polybenzoxazine gel obtained in step (4) is transferred to a container filled with 98% ethanol, and after the lid is closed, the container is placed in a 60°C water bath for solvent replacement, and the solvent is replaced every 6 hours for three times; after the solvent replacement is completed, the gel is cooled to room temperature to obtain the final Kevlar-polybenzoxazine gel;

[0060] (7) The final Kevlar-polybenzoxazine gel obtained in step (6) is placed in a CO2 supercritical fluid drying device at a drying pressure of 13 MPa, a drying temperature of 50°C, and a drying time of 10 h to obtain a Kevlar-polybenzoxazine aerogel.

[0061] The density of the final prepared Kevlar-polybenzoxazine aerogel is 0.147 g cm -3 , thermal conductivity is 0.0182 Wm -1 K -1 , the compressive stress is 2.041 MPa at 3% strain.

[0062] Embodiment 3:

[0063] A method for preparing a Kevlar-polybenzoxazine aerogel comprises the following steps:

[0064] (1) Pour 0.1 g of Kevlar nanofiber into 99.9 g of DMF with a concentration of 10 wt% potassium hydroxide for dispersion, and stir at 60 °C until uniformly dispersed to obtain a Kevlar nanofiber solution with a concentration of 0.1 wt%, which is recorded as solution A.

[0065] (2) 5 g of bisphenol A benzoxazine monomer of structural formula II was fully dissolved in 95 g of DMF to obtain 100 g of 5 wt% bisphenol A benzoxazine monomer solution, and then 0.922 ml of hydrochloric acid was added to the benzoxazine monomer solution as an initiator (i.e., the molar ratio of bisphenol A benzoxazine monomer to hydrochloric acid was 1:1), and the mixture was stirred at room temperature for 15 min to obtain a polybenzoxazine sol, which was recorded as solution B;

[0066] (3) mixing solution A obtained in step (1) with solution B obtained in step (2), and stirring at room temperature for 5 min to obtain a Kevlar-polybenzoxazine sol, wherein the mass ratio of solution A to solution B is 0.2;

[0067] (4) the Kevlar-polybenzoxazine sol obtained in step (3) is placed at room temperature and allowed to stand for about 30 hours, and then a gelation reaction occurs, causing the bisphenol A-type benzoxazine monomer to undergo ring-opening polymerization to obtain an initial Kevlar-polybenzoxazine gel;

[0068] (5) placing the initial Kevlar-polybenzoxazine gel obtained in step (4) at room temperature for 48 hours for aging to obtain an aged Kevlar-polybenzoxazine gel;

[0069] (6) The initial Kevlar-polybenzoxazine gel obtained in step (4) is transferred to a container filled with 98% ethanol, and after the lid is closed, the container is placed in a 60°C water bath for solvent replacement, and the solvent is replaced every 6 hours for three times; after the solvent replacement is completed, the gel is cooled to room temperature to obtain the final Kevlar-polybenzoxazine gel;

[0070] (7) The final Kevlar-polybenzoxazine gel obtained in step (6) is placed in a CO2 supercritical fluid drying device at a drying pressure of 13 MPa, a drying temperature of 50°C, and a drying time of 10 h to obtain a Kevlar-polybenzoxazine aerogel.

[0071] The density of the final prepared Kevlar-polybenzoxazine aerogel is 0.109 g cm -3 , thermal conductivity is 0.0187 Wm -1 K -1 , the compressive stress is 1.990 MPa at 3% strain.

[0072] Embodiment 4:

[0073] A method for preparing a Kevlar-polybenzoxazine aerogel comprises the following steps:

[0074] (1) Pour 5.5 g of Kevlar nanofibers into 94.5 g of DMF with a concentration of 10 wt % potassium hydroxide for dispersion, and stir at 60 ° C until uniformly dispersed to obtain a Kevlar nanofiber solution with a concentration of 5.5 wt %, which is recorded as solution A;

[0075] (2) 15 g of bisphenol A benzoxazine monomer of structural formula II was fully dissolved in 85 g of DMF to obtain 100 g of 15 wt% bisphenol A benzoxazine monomer solution, and then 2.766 ml of hydrochloric acid was added to the benzoxazine monomer solution as an initiator (i.e., the molar ratio of bisphenol A benzoxazine monomer to hydrochloric acid was 1:1), and the mixture was stirred at room temperature for 15 min to obtain a polybenzoxazine sol, which was recorded as solution B;

[0076] (3) mixing the solution A obtained in step (1) with the solution B obtained in step (2), and further stirring at room temperature for 5 minutes to obtain a Kevlar-polybenzoxazine sol, wherein the mass ratio of solution A to solution B is 0.6;

[0077] (4) the Kevlar-polybenzoxazine sol obtained in step (3) is placed at room temperature and allowed to stand for about 20 hours, and then a gelation reaction occurs, causing the bisphenol A-type benzoxazine monomer to undergo ring-opening polymerization to obtain an initial Kevlar-polybenzoxazine gel;

[0078] (5) placing the initial Kevlar-polybenzoxazine gel obtained in step (4) at room temperature for 48 hours for aging to obtain an aged Kevlar-polybenzoxazine gel;

[0079] (6) The initial Kevlar-polybenzoxazine gel obtained in step (4) is transferred to a container filled with 98% ethanol, and after the lid is closed, the container is placed in a 60°C water bath for solvent replacement, and the solvent is replaced every 6 hours for three times; after the solvent replacement is completed, the gel is cooled to room temperature to obtain the final Kevlar-polybenzoxazine gel;

[0080] (7) The final Kevlar-polybenzoxazine gel obtained in step (6) is placed in a CO2 supercritical fluid drying device at a drying pressure of 13 MPa, a drying temperature of 50°C, and a drying time of 10 h to obtain a Kevlar-polybenzoxazine aerogel.

[0081] The density of the final prepared Kevlar-polybenzoxazine aerogel is 0.197 g cm -3 , thermal conductivity is 0.0291 Wm -1 K -1 , the compressive stress is 3.974 MPa at 3% strain.

[0082] Embodiment 5:

[0083] A method for preparing a Kevlar-polybenzoxazine aerogel comprises the following steps:

[0084] (1) Pour 10 g of Kevlar nanofibers into 90 g of DMF with a concentration of 10 wt% potassium hydroxide for dispersion, and stir at 60 °C until uniformly dispersed to obtain a Kevlar nanofiber solution with a concentration of 10 wt%, which is recorded as solution A.

[0085] (2) 5 g of bisphenol A benzoxazine monomer of structural formula III was fully dissolved in 95 g of DMF to obtain 100 g of 5 wt% bisphenol A benzoxazine monomer solution, and then 0.922 ml of hydrochloric acid was added to the benzoxazine monomer solution as an initiator (i.e., the molar ratio of bisphenol A benzoxazine monomer to hydrochloric acid was 1:1), and the mixture was stirred at room temperature for 15 min to obtain a polybenzoxazine sol, which was recorded as solution B;

[0086] (3) mixing solution A obtained in step (1) with solution B obtained in step (2), and stirring at room temperature for 5 min to obtain a Kevlar-polybenzoxazine sol, wherein the mass ratio of solution A to solution B is 1;

[0087] (4) The Kevlar-polybenzoxazine sol obtained in step (3) is placed at room temperature and allowed to stand for about 24 hours to undergo a gelation reaction, causing the bisphenol A-type benzoxazine monomer to undergo ring-opening polymerization to obtain an initial Kevlar-polybenzoxazine gel;

[0088] (5) placing the initial Kevlar-polybenzoxazine gel obtained in step (4) at room temperature for 48 hours for aging to obtain an aged Kevlar-polybenzoxazine gel;

[0089] (6) The initial Kevlar-polybenzoxazine gel obtained in step (4) is transferred to a container filled with 98% ethanol, and after the lid is closed, the container is placed in a 60°C water bath for solvent replacement, and the solvent is replaced every 6 hours for three times; after the solvent replacement is completed, the gel is cooled to room temperature to obtain the final Kevlar-polybenzoxazine gel;

[0090] (7) The final Kevlar-polybenzoxazine gel obtained in step (6) is placed in a CO2 supercritical fluid drying device at a drying pressure of 13 MPa, a drying temperature of 50°C, and a drying time of 10 h to obtain a Kevlar-polybenzoxazine aerogel.

[0091] The density of the final prepared Kevlar-polybenzoxazine aerogel is 0.252 g cm -3 , thermal conductivity is 0.0231 Wm -1 K -1 , the compressive stress is 3.871 MPa at 3% strain.

[0092] Embodiment 6:

[0093] A method for preparing a Kevlar-polybenzoxazine aerogel comprises the following steps:

[0094] (1) Pour 0.1 g of Kevlar nanofiber into 99.9 g of DMF with a concentration of 10 wt% potassium hydroxide for dispersion, and stir at 60 °C until uniformly dispersed to obtain a Kevlar nanofiber solution with a concentration of 0.1 wt%, which is recorded as solution A.

[0095] (2) 25 g of bisphenol A benzoxazine monomer of structural formula II was fully dissolved in 75 g of DMF to obtain 100 g of 25 wt% bisphenol A benzoxazine monomer solution, and then 4.609 ml of hydrochloric acid was added to the benzoxazine monomer solution as an initiator (i.e., the molar ratio of bisphenol A benzoxazine monomer to hydrochloric acid was 1:1), and the mixture was stirred at room temperature for 15 min to obtain a polybenzoxazine sol, which was recorded as solution B;

[0096] (3) mixing solution A obtained in step (1) with solution B obtained in step (2), and further stirring at room temperature for 5 min to obtain a Kevlar-polybenzoxazine sol, wherein the mass ratio of solution A to solution B is 1;

[0097] (4) the Kevlar-polybenzoxazine sol obtained in step (3) is placed at room temperature and allowed to stand for about 20 hours, and then a gelation reaction occurs, causing the bisphenol A-type benzoxazine monomer to undergo ring-opening polymerization to obtain an initial Kevlar-polybenzoxazine gel;

[0098] (5) placing the initial Kevlar-polybenzoxazine gel obtained in step (4) at room temperature for 48 hours for aging to obtain an aged Kevlar-polybenzoxazine gel;

[0099] (6) The initial Kevlar-polybenzoxazine gel obtained in step (4) is transferred to a container filled with 98% ethanol, and after the lid is closed, the container is placed in a 60°C water bath for solvent replacement, and the solvent is replaced every 6 hours for three times; after the solvent replacement is completed, the gel is cooled to room temperature to obtain the final Kevlar-polybenzoxazine gel;

[0100] (7) The final Kevlar-polybenzoxazine gel obtained in step (6) is placed in a CO2 supercritical fluid drying device at a drying pressure of 13 MPa, a drying temperature of 50°C, and a drying time of 10 h to obtain a Kevlar-polybenzoxazine aerogel.

[0101] The density of the final prepared Kevlar-polybenzoxazine aerogel is 0.162 g cm -3 , thermal conductivity is 0.0271 Wm -1 K -1 , the compressive stress is 2.701 MPa at 3% strain.

[0102] Embodiment 7~81:

[0103] The process parameters used in Examples 7 to 81 are shown in Tables 2 to 9, and the experimental process parameters not specified in the remaining tables are the same as those in Example 1.

[0104] The above preparation process is as follows:

[0105] The purpose of adding the solvent and potassium hydroxide in step (1) is to dissolve the Kevlar nanofibers;

[0106] Step (2) mainly prepares a benzoxazine monomer solution, and the purpose of adding a certain amount of hydrochloric acid is to initiate polymerization of the benzoxazine monomer to obtain a polybenzoxazine sol;

[0107] Step (3) mixing solution A with solution B is to obtain Kevlar-polybenzoxazine sol;

[0108] Step (4) the Kevlar-polybenzoxazine sol undergoes a sol-gel transition at room temperature to obtain an initial Kevlar-polybenzoxazine gel;

[0109] Step (5) is to further improve the skeleton strength of the initial Kevlar-polybenzoxazine gel by aging to obtain an aged Kevlar-polybenzoxazine gel;

[0110] The purpose of performing solvent replacement at a certain temperature in step (6) is to better replace the organic solvent and obtain the final Kevlar-polybenzoxazine gel;

[0111] The temperature and pressure used in the supercritical fluid drying method used in step (7) are basic parameters set to maintain the supercritical fluid state of carbon dioxide.

[0112] Specifically, the Kevlar-polybenzoxazine aerogel prepared from the bisphenol A benzoxazine monomer of structural formula I corresponds to Examples 1 to 27; Examples 28 to 54 correspond to the bisphenol A benzoxazine monomer of structural formula II; and Examples 55 to 81 correspond to the bisphenol A benzoxazine monomer of structural formula III.

[0113] The difference between Examples 1 to 3 is that the mass ratio between solution A and solution B remains unchanged (0.2), and the mass concentration of bisphenol A type benzoxazine monomer remains unchanged (5wt%), and the effect of the change of the mass concentration of Kevlar nanofibers (0.1wt%~10wt%) on the properties of Kevlar-polybenzoxazine aerogel is studied. The results show that as the mass concentration of Kevlar nanofibers increases, the density and thermal conductivity of the prepared Kevlar-polybenzoxazine aerogel increase, and the compressive strength increases.

[0114] Examples 1 to 9 are based on Examples 1 to 3, with the mass ratio between solution A and solution B unchanged (0.2), and the mass concentration of Kevlar nanofibers unchanged (0.1wt%, 5.5wt%, 10wt%), to study the effect of the mass concentration of bisphenol A benzoxazine monomer solution (5wt% to 25wt%) on the performance of Kevlar-polybenzoxazine aerogel. The results show that when the mass concentration of Kevlar nanofibers in the system is the same, as the mass concentration of bisphenol A benzoxazine monomer solution increases, the density and thermal conductivity of the prepared Kevlar-polybenzoxazine aerogel increase, and the compressive strength increases.

[0115] Examples 1 to 27 are based on Examples 1 to 9, with the mass concentration of Kevlar nanofibers unchanged (0.1wt%, 5.5wt%, 10 wt%) and the mass concentration of bisphenol A benzoxazine monomer solution unchanged (5wt%, 15wt%, 25wt%), to study the effect of the change in the mass ratio between solution A and solution B (0.2 to 1) on the performance of Kevlar-polybenzoxazine aerogel. The results show that when the mass concentration of Kevlar nanofibers and the mass concentration of bisphenol A benzoxazine monomer in the system are the same, as the mass ratio between solution A and solution B increases, the density and thermal conductivity of the prepared Kevlar-polybenzoxazine aerogel increase, and the compressive strength increases.

[0116] For Examples 28 to 54 (Structural Formula II) and Examples 55 to 81 (Structural Formula III), the influence of parameter changes between these Examples on the performance of Kevlar-polybenzoxazine aerogel is the same as that of Examples 1 to 27 (Structural Formula I).

[0117] Therefore, as long as the types of alkaline substances, acids, organic solvents, gel time, replacement time, aging and solvent replacement time, replacement solvent types, supercritical fluid drying methods, etc. change within the scope of the invention, the influence on the density, thermal conductivity and compressive strength of Kevlar-polybenzoxazine aerogel is negligible. The main factors affecting the density, thermal conductivity and compressive strength of Kevlar-polybenzoxazine aerogel are the types of bisphenol A-type benzoxazine monomers (the mechanical strength of Kevlar-polybenzoxazine aerogel prepared by using a chemical structure containing more OH is better than that of Kevlar-polybenzoxazine aerogel prepared by using a chemical structure containing less OH), the mass concentration of Kevlar nanofiber solution, the mass concentration of bisphenol A-type benzoxazine monomer solution, and the mass ratio of solution A to solution B.

[0118] Table 1: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0119]

[0120] Table 2: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0121]

[0122] Table 3: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0123]

[0124] Table 4: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0125]

[0126] Table 5: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0127]

[0128] Table 6: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0129]

[0130] Table 7: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0131]

[0132] Table 8: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0133]

[0134] Table 9: Preparation process parameters and performance parameters of polybenzoxazine aerogel

[0135]

[0136] From the data in Table 1, it can be seen that when the monomer structural formula, the mass concentration of the bisphenol A type benzoxazine monomer solution, and the mass ratio of solution A to solution B of the Kevlar-polybenzoxazine aerogel prepared by the method of the present invention are constant, the density, thermal conductivity and compressive strength increase with the increase of the mass concentration of the Kevlar nanofiber solution.

[0137] When the monomer structure, the mass concentration of Kevlar nanofibers, and the mass ratio of solution A to solution B are constant, the density, thermal conductivity, and compressive strength increase with the increase of the mass concentration of bisphenol A-type benzoxazine monomer solution. When the monomer structure, the mass concentration of Kevlar nanofibers, and the mass concentration of bisphenol A-type benzoxazine monomer solution are constant, the density, thermal conductivity, and compressive strength increase with the increase of the mass ratio of solution A to solution B.

[0138] When the mass concentration of Kevlar nanofibers, the mass concentration of bisphenol A-type benzoxazine monomers, and the mass ratio of solution A to solution B are constant, the change in the structural formula has little effect on the density and thermal conductivity of Kevlar-polybenzoxazine aerogel, while for mechanical properties, the compressive strength of structural formula III> the compressive strength of structural formula II> the compressive strength of structural formula I. The present invention not only proposes a method for preparing Kevlar-polybenzoxazine aerogel, but also the obtained product aerogel has ultra-low thermal conductivity, indicating its efficient thermal insulation performance. Therefore, the invention will have broad application prospects in the field of building thermal insulation.

[0139] Comparative Example 1:

[0140] The difference between Comparative Example 1 and Example 1 is that the addition of Kevlar nanofibers in step (1) is omitted, and the other steps are the same as those in Example 1;

[0141] The density of the obtained polybenzoxazine aerogel is 0.124 g cm -3 , thermal conductivity is 0.0223 W m -1 K -1 , the compressive stress is 2.011 MPa at 3% strain.

[0142] It shows that the addition of Kevlar nanofibers helps to reduce the thermal conductivity of aerogels, while having relatively little effect on the density and mechanical strength of aerogels.

[0143] Comparative Example 2:

[0144] The difference between Comparative Example 2 and Example 1 is that the concentration of the Kevlar nanofiber solution in step (1) is 0.05 wt %, and the rest is the same as Example 1;

[0145] The Kevlar-polybenzoxazine sol prepared according to this concentration cannot obtain a stable Kevlar-polybenzoxazine gel under the reaction conditions mentioned in the present invention.

[0146] This indicates that the addition of a small amount of Kevlar nanofibers will be detrimental to the gelation reaction and a stable gel cannot be obtained.

[0147] Comparative Example 3:

[0148] The difference between Comparative Example 3 and Example 1 is that the concentration of the Kevlar nanofiber solution in step (1) is 11 wt %, and the rest is the same as Example 1;

[0149] The density of the obtained Kevlar-polybenzoxazine aerogel is 0.173 g cm -3 , thermal conductivity is 0.0312 W m - 1 K -1 , the compressive stress is 2.446 MPa at 3% strain.

[0150] It shows that the addition of excessive Kevlar nanofibers will significantly increase the density and thermal conductivity of Kevlar-polybenzoxazine aerogel, while the improvement in mechanical strength is relatively unobvious.

[0151] It will be clear to those skilled in the art that the scope of the present invention is not limited to the examples discussed above, and that several changes and modifications may be made thereto without departing from the scope of the present invention as defined in the appended claims. Although the present invention has been illustrated and described in detail in the drawings and the specification, such illustration and description are merely illustrative or schematic and not restrictive. The present invention is not limited to the disclosed embodiments.

[0152] By studying the drawings, the description and the claims, those skilled in the art can understand and implement variations of the disclosed embodiments when implementing the invention. In the claims, the term "comprising" does not exclude other steps or elements, and the indefinite article "a" or "an" does not exclude a plurality. The fact that certain measures are cited in mutually different dependent claims does not mean that a combination of these measures cannot be used to advantage. Any reference signs in the claims do not constitute a limitation of the scope of the invention.

Claims

1. A method for preparing a Kevlar-polybenzoxazine aerogel, characterized in that: The following steps are involved: (1) Pour Kevlar nanofibers into an organic solvent containing an alkaline substance for dispersion, and stir at 20° C. to 60° C. until the fibers are uniformly dispersed, to obtain a Kevlar nanofiber solution having a mass concentration of 0.1 wt % to 10 wt %, as solution A; The chemical structural formula of the Kevlar nanofiber is: ; The alkaline substance is one of potassium hydroxide, sodium hydroxide, triethylamine, tetramethylethylenediamine, sodium tert-butoxide, potassium tert-butoxide, potassium hexamethyldisilazide, and sodium hexamethyldisilazide; The concentration of the alkaline substance in the organic solvent is 0.1 wt%~20 wt%; The organic solvent is one of DMF, DMSO or NMP; (2) Stirring a bisphenol A benzoxazine monomer at room temperature and fully dissolving it in an organic solvent to prepare a bisphenol A benzoxazine monomer solution having a mass concentration of 5 wt% to 25 wt%, and then adding an acid substance as an initiator of the benzoxazine monomer, wherein the amount of the acid substance is prepared according to a molar ratio of bisphenol A benzoxazine monomer to the acid substance of 1:(1 to 3); stirring at 10°C to 30°C for 10 min to 15 min to obtain a polybenzoxazine sol, which is used as solution B; The structural formula of the bisphenol A type benzoxazine monomer is as follows: When R1=OH, R2=CH3, it is bisphenol A type benzoxazine monomer structural formula Ⅰ; When R1=OH, one of R2 is OH and the other is CH3, it is bisphenol A type benzoxazine monomer structural formula II; When R1=OH, R2=OH, it is bisphenol A type oxazine monomer structural formula III; The acid substance is one of hydrochloric acid, tannic acid, p-toluenesulfonic acid and boric acid; (3) mixing the solution A obtained in step (1) and the solution B obtained in step (2) in a mass ratio of (0.2-1):1, and stirring at 10°C-30°C for 5-10 minutes to obtain a Kevlar-polybenzoxazine sol; (4) The Kevlar-polybenzoxazine sol obtained in step (3) is transferred into a mold, sealed, and placed at 10°C to 30°C for gelation. After standing for 15 h to 72 h for gelation, an initial Kevlar-polybenzoxazine gel is obtained; (5) aging the initial Kevlar-polybenzoxazine gel obtained in step (4) at 10° C. to 30° C. for 24 h to 96 h to obtain an aged Kevlar-polybenzoxazine gel; (6) transferring the aged Kevlar-polybenzoxazine gel obtained in step (5) into a solvent containing a replacement solvent, covering the container with a lid and placing the container in a water bath, and performing solvent replacement at 50° C. to 70° C. to obtain a final Kevlar-polybenzoxazine gel; The replacement solvent is one of ethanol, acetone, isopropanol, and tert-butanol, the mass concentration of the replacement solvent is ≥95wt%, the number of solvent replacements is 2 to 4 times, and the time interval is 6 h to 12 h; (7) The final Kevlar-polybenzoxazine gel obtained in step (6) is subjected to CO2 supercritical fluid drying, wherein the CO2 supercritical fluid drying has a drying pressure of 8 MPa to 18 MPa, a temperature of 40°C to 60°C, and a drying time of 6 h to 18 h to obtain a Kevlar-polybenzoxazine aerogel having a density of 0.109 g cm -3 ~0.252 g cm -3 , thermal conductivity is 0.0182 W m -1 K -1 ~0.0343 W m -1 K -1 , the compressive stress is 1.871 MPa~3.974 MPa at 3% strain.

2. The method for preparing a Kevlar-polybenzoxazine aerogel according to claim 1, characterized in that: In step (1), the mass concentration of the Kevlar nanofiber solution is 5.5 wt %; the alkaline substance is potassium hydroxide; the concentration of the alkaline substance in the organic solvent is 10 wt %; the organic solvent is DMF; stirring is performed at 50° C. until uniform dispersion.

3. The method for preparing a Kevlar-polybenzoxazine aerogel according to claim 1, characterized in that: In step (2), the polybenzoxazine sol is obtained after stirring for 10 min.

4. The method for preparing a Kevlar-polybenzoxazine aerogel according to claim 1, characterized in that: In step (3), the mixture is mixed at a mass ratio of 0.6:1 and stirred for 10 min.

5. The method for preparing a Kevlar-polybenzoxazine aerogel according to claim 1, characterized in that: In step (5), aging is performed at room temperature for 48 h.

6. The method for preparing a Kevlar-polybenzoxazine aerogel according to claim 1, characterized in that: In step (6), solvent replacement is performed at 60°C, the replacement solvent is ethanol or acetone, the number of solvent replacements is 3 times, and the time interval is 6 hours.

7. The method for preparing a Kevlar-polybenzoxazine aerogel according to claim 1, characterized in that: In step (7), the drying pressure during CO2 supercritical fluid drying is 12 MPa~15 MPa, the temperature is 45℃~55℃, and the time is 8 h~10 h.

8. A Kevlar-polybenzoxazine aerogel, characterized in that: The Kevlar-polybenzoxazine aerogel prepared by the method according to any one of claims 1 to 7 has a three-dimensional nanoporous network structure, ultra-low thermal conductivity and thermal insulation performance, and has a blocking effect on solid heat transfer and gas heat transfer. The density is 0.109 g cm -3 ~0.252 g cm -3 , thermal conductivity is 0.0182 W m -1 K -1 ~0.0343 W m -1 K -1 , and has the following mechanical properties: the compressive stress is 1.871 MPa~3.974 MPa at 3% strain.

Citation Information

Patent Citations

  • High-performance aramid fiber / PBO nano insulation paper and preparation method thereof

    CN117779525A

  • heat-curable, thermally expandable moldings with long fibers or fiber structures

    DE102007025870A1